OP0184 Efficacy and Safety of Tabalumab in Patients with Systemic Lupus Erythematosus (SLE): Results from 2 Phase 3, 52-Week, Multicenter, Randomized, Placebo-Controlled Trials. (9th June 2015) - Isenberg, D.; Merrill, J.; Hoffman, R.; Linnik, M.; Morgan-Cox, M.; Veenhuizen, M.; Iikuni, N.; Dickson, C.; Silk, M.; Wallace, D.; Dörner, T.
Abstract : Background: Tabalumab is a human IgG4 monoclonal antibody that binds and neutralizes membrane and soluble BAFF. Objectives: Two trials, involving >2000 patients (pts) with SLE, evaluated the efficacy and safety of subcutaneous tabalumab + standard of care (SoC) versus placebo (pbo) + SoC at 52 weeks (wks). Methods: ANA-positive pts were enrolled with active, moderate-to-severe SLE (baseline SELENA-SLEDAI score ≥6). Pts with severe active renal or CNS disease were excluded. Pts received a loading dose (240 mg or pbo) at Wk 0, followed by 120 mg tabalumab every 2 wks (120 Q2W), 4 wks (120 Q4W), or pbo. Primary endpoint: proportion of pts achieving SLE Responder Index 5 (SRI-5) response at Wk 52. Key secondary endpoints: time to severe flare, corticosteroid sparing, and worst fatigue over last 24 hours (hrs). Subgroup analyses based on background SoC, complement, and anti-dsDNA were conducted. Results: Baseline disease activity and clinical characteristics were balanced across groups in both trials. SRI-5 was not met in Trial 1, but was met in Trial 2 for the 120 Q2W dose (p=0.002; Table ). Key secondary efficacy endpoints did not achieve statistical significance. Subgroup analysis showed that baseline antimalarial (AM) use did not reduce SRI-5 response rates. Reduction in anti-dsDNA was observed as well as increases in complement C3 and C4 and reduction in total B cells and immunoglobulins (Ig). The safety profile of the tabalumab and pbo groups was similar across both trials. Conclusions: Tabalumab had biologic activity consistent with BAFF inhibition, as shown by anti-dsDNA, complement, B cell, and Ig changes. The primary endpoint was met in 1 of 2 trials for the 120 Q2W dose. Disclosure of Interest: D. Isenberg Consultant for: Eli Lilly and Company, J. Merrill Grant/research support from: GlaxoSmithKline, Consultant for: Eli Lilly and Company, GlaxoSmithKline, Anthera Pharmaceuticals, EMD Serono, Speakers bureau: GlaxoSmithKline, R. Hoffman Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, M. Linnik Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, M. Morgan-Cox Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, M. Veenhuizen Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, N. Iikuni Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, C. Dickson Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, M. Silk Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, D. Wallace Consultant for: Eli Lilly and Company, T. Dörner Consultant for: Eli Lilly and Company, UCB, Roche/Chugai Pharmaceutical Co. Ltd., Sanofi